The Burden of Non-Communicable Diseases in Middle Age Population of Karachi, Pakistan - P. Ali Khowaja, Farah Naz, Nooruddin Khowaja, S. Masood Hussain, Abdul Samad, Pir A. Hayee, M. Zaman Shaikh, S Naseem (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate burden of diabetes in middle age population (36-56 years) and the associated clinical and participant characteristics living in Karachi. Study design: Retrospective study. Place and duration of study: Two GP Clinics @ Karachi over a period of 6 Months from 1st September 2020 to 28th February 2021. Methodology: Three hundred and eighteen type II diabetic patients were registered. Complete history and physical examination done for all registered patients. The age, sex, occupation, address, family history of diabetes, addiction was recorded. Results: Two hundred and twenty seven (71.4%) were females. The mean age was 46.7±7.1. The burden of diabetes was significant (p <0.001) in the rural population (54.7%). There is a higher prevalence of diabetes in Pashtun population of Karachi than other Ethnicities 96 (30.2%). There is significant positive correlation in patients with poor, the median HbA1c was 8.4. Conclusion: This study determined the burden of diabetes mellitus in middle age group (36-56 years) and established its association with obesity, sedentary lifestyle and high HbA1c levels.